2010
DOI: 10.1038/leu.2010.195
|View full text |Cite
|
Sign up to set email alerts
|

Gfi1 and Gfi1b: key regulators of hematopoiesis

Abstract: Transcription factor Growth factor independence 1 (Gfi1) is required for multilineage blood cell development, from stem and progenitor cells to differentiated lymphoid and myeloid cells. Gfi1 expression is rapidly induced by cytokines that control both the adaptive and innate immune systems. Gfi1 itself represses the expression of genes implicated in cell survival, proliferation and differentiation. Changes in Gfi1 expression and function have not only been implicated in neutropenia, allergy, autoimmunity and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
158
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 185 publications
(166 citation statements)
references
References 106 publications
(160 reference statements)
8
158
0
Order By: Relevance
“…Intriguingly, a hallmark of Gfi1-null mice is inhibited granulocytic differentiation together with enhanced monocytic differentiation. 43 Gfi1-null mice further display myeloid progenitor expansion associated with Hoxa9 overexpression, 28 similar to our LSD1-kd model. As Gfi1 and LSD1 are known to directly interact 11 and LSD1-kd mice mirror myeloid abnormalities of Gfi1-deficient mice, LSD1 presumably represents a key mediator of Gfi1 function in myelopoiesis.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Intriguingly, a hallmark of Gfi1-null mice is inhibited granulocytic differentiation together with enhanced monocytic differentiation. 43 Gfi1-null mice further display myeloid progenitor expansion associated with Hoxa9 overexpression, 28 similar to our LSD1-kd model. As Gfi1 and LSD1 are known to directly interact 11 and LSD1-kd mice mirror myeloid abnormalities of Gfi1-deficient mice, LSD1 presumably represents a key mediator of Gfi1 function in myelopoiesis.…”
Section: Discussionsupporting
confidence: 73%
“…It was shown that Gfi1 and Gfi1b are both negative regulators of HSC proliferation. 43 However, Gfi1-deficient HSCs displayed impaired self-renewal capacity in competitive repopulation assays whereas the self-renewal of Gfi1b-deficient HSCs remained unaltered. 40 Interestingly, conditional deletion of Gfi1b resulted in expanded phenotypic HSCs, which parallels our findings in LSD1-kd mice.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with a prosurvival role of Gfi1 observed in other cell types (8,21), deficiency of Gfi1 modestly elevated apoptosis of CD4SP thymocytes and rendered them a competitive disadvantage. However, forced expression of the Bcl2 transgene or deletion of Bim did not affect the generation of nT reg cells in Gfi1 CD4 mice.…”
Section: Discussionsupporting
confidence: 49%
“…S1A). Given a prominent role of Gfi1 in the development of multiple hematopoietic lineages (8,21), it remained possible that the expansion of Gfi1 −/− nT reg cells was secondary to defective early development and/or influences by nonlymphoid cells. Hence, we crossed loxPflanked Gfi1 alleles (Gfi1 fl/fl ) with two Cre lines, the hCD2-iCre and CD4-Cre transgenic mice, in which Cre expression was initiated at the early and late DN stages, respectively (called Gfi1 hCD2 and Gfi1 CD4 ) (22,23).…”
Section: Gfi1mentioning
confidence: 99%
See 1 more Smart Citation